Postcensorship in Streaming: Political Alienation of Millenials and Centennials Toward Audiovisual Productions - Fernández-Rodríguez, Carlos; Romero-Rodríguez, Luis M.; Castillo-Abdul, Bárbara (Convergencia Revista de Ciencias Sociales, 2024)
This study examines the degree to which political alienation viewers consider themselves to have audiovisual productions. To understand the preferences of millennials and centennials in the Spanish-speaking world, a survey was conducted with 998 individuals from Spain and Mexico, two countries with high rates of OTT consumption. The survey revealed that young people feel justified in expressing their discontent with audiovisual productions on social media, potentially leading to an "audience dictatorship, " which stifles creative freedom and expression. In this sense, young people with discursive power in social networks to change and censor production see it as plausible to use this channel as a denunciation or complaint.